Estimates of Combining Ability and Heterosis for Yield and Its Related Traits in Pearl Millet Inbred Lines under Downy Mildew Prevalent Areas of Senegal - Ghislain Kanfany; Amadou Fofana; Pangirayi Tongoona; Agyemang Danquah; Samuel Offei; Eric Danquah; Ndiaga Cisse (International Journal of Agronomy)
Pearl millet is an important cereal crop for smallholder farmers’ food security in West and Central Africa. However, its production has stagnated due to several factors such as the continuous use of local populations. A set of 17 inbred lines was crossed with Sosat C 88 and Souna 3 following a line × tester mating design. The F1 hybrids, their parents, and a check were evaluated in Bambey and Nioro research stations during the rainy season of 2017. Data on downy mildew incidence, plant height, flowering time, panicle length and diameter, productive tillers, thousand-grain weight, panicle, and grain yield were recorded. GCA and SCA mean squares were significant for most of the traits indicating that both additive and nonadditive gene effects were involved in the control of the inheritance of these traits. However, the contribution of GCA to total mean squares was higher than that of SCA for all the traits, providing that additive gene action was more important in their inheritance. The top-cross hybrid IBL155-2-1 × Sosat C 88 exhibited negative and significant SCA effects for downy mildew incidence, flowering time, and plant height. Lines IBL003-B-1, IBL091-1-1, IBL095-4-1, IBL110-B-1, and IBL 206-1-1 had positive GCA effects for grain yield and negative GCA effects for downy mildew, flowering time, and plant height. These lines can be used as parents to create synthetic varieties or hybrids.